Physical activity: practice this idea - Guimarães, Guilherme Veiga; Ciolac, Emmanuel Gomes [UNESP] (My University, 2014)
Sedentary habits or insufficient activities to promote health benefits can influence the occurrence of chronic diseases. The cardiovascular risk factors arise, at least partially, from the individual-environment interaction during life, and worsen with aging and lack of physical exercise. Health promotion and prevention are among the greatest challenges of public health policies. However, physical activity turns out to be rarely recommended and, thus have a very poor adhesion. In spite of consensus about the benefits of physical activity in both primary and secondary prevention, only 32% of adults and 66% of children and adolescents, according to Healthy People 2010 guideline, practice leisure-time physical activity. Thus, the regular practice of physical activity and healthy habits require changes in basic concepts in government and social policies. The higher involvement of public and private sectors related to health and education, the more expressive would be the reduction in socioeconomic costs and the improvement in quality of life.
Keywords: Exercise; Barrier; Physical activity